Ojciec jako rodziciel - Gębka, Mikołaj (Wydawnictwo Naukowe UAM, 2007)
The paper discusses a new aspect of the role of the father, the presence of the father during the childbirth. The author's research shows evidence that this role has a positive influence on other roles of the father, and works towards strengthening of the marriage bonds.
Father as a parent